"R" is for research ; and, "R" is for research. Library lessons - Buzzeo, Toni.; Wong, Nicole (Fort Atkinson, Wis. : Upstart Books, 2008)
A picture book and library lesson booklet that introduce basic research concepts.
Includes bibliographical references.
Professional
Keywords: Reading; Creative activities and seat work; Teaching -- Aids and devices; Reading; Creative activities; Teaching -- Aids and devices